Linguistic Landscape on public signs in Pakse City, Champasak Province, Laos: ภูมิทัศน์ภาษาบนป้ายสาธารณะในนครปากเซ แขวงจำปาสัก สาธารณรัฐประชาธิปไตยประชาชนลาว - Worrahin, Papawarin; Jitbanjong , Dutchat; Wannaudorn , Smai (Mekong-Salween Civilization Studies Journal, 2025)
This study aims to examine language use and writing styles on public signs in Pakse, Champasak Province, Lao People's Democratic Republic, based on the concept of linguistic landscape by Landry and Bourhis (1997). The analysis covers a total of 858 public signs, both permanent and temporary, created by government and private sectors. Results show the presence of eight languages, with Lao being the most prevalent, accounting for 56.17% of all the signs. In terms of language format, four patterns were identified, with bilingual signs being the most common at 57.23%. As for writing style, four types were observed, with monolingual signs being the highest at 36.48%. The study highlights the role of the Lao language as the national language, essential for communication in the area, while other languages play significant roles in tourism and commerce. Additionally, the findings reflect key factors influencing language use and writing styles on public signs in Pakse, including: (1) Government policy, which mandates Lao as the primary language on public signs to promote national identity and unity; (2) Integration into the global society and tourism economy, leading to the increased use of English and other foreign languages on public signs, particularly in business and service sectors to accommodate tourists and investors; and (3) Socioeconomic, political, and cultural relations at the regional level, particularly the influence of Chinese, Vietnamese, and Thai, which reflects economic and trade interactions with neighboring countries. The linguistic landscape of Pakse thus reflects the coexistence of diverse languages and cultures, shaped by the social and economic context and language policies that promote the use of Lao alongside foreign languages in appropriate settings.